The Concept of Tazkiyatun Nafs in Tafsir Al-Misbah and Its Relevance to the Millennial Generation's Mentality - Sabrun Jamil; Faaiz Tsabbitul Aqdam; Fanny Amalia Agusti; Raja Maya Nur Azhara; Ririn; Lailatul Mardiah; Fatimah Nurul Fadhillah; Raja Nella Kusuma Dewi (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2026)
The rapid development of digital technology and social transformation has created new psychological challenges for the millennial generation, including emotional instability, identity uncertainty, excessive dependence on social validation, and loss of spiritual meaning. This study aims to analyze the concept of tazkiyatun nafs in Tafsir Al-Misbah by M. Quraish Shihab and examine its relevance for strengthening millennial mental resilience. This research employs a qualitative approach with a library research design through textual analysis and thematic interpretation. The primary data source is Tafsir Al-Misbah, supported by academic literature on Qur’anic studies, Islamic psychology, spiritual well being, and contemporary mental health. Data were analyzed using thematic analysis by identifying, categorizing, and interpreting key themes related to soul purification, spiritual development, emotional regulation, and psychological transformation. The findings reveal that tazkiyatun nafs in Tafsir Al-Misbah consists of three interconnected dimensions: purification of negative internal tendencies, development of spiritual and moral qualities, and transformation toward inner peace (nafs al-mu?ma’innah). This concept provides a relevant Islamic framework for addressing millennial mental challenges by strengthening self-awareness, emotional control, spiritual resilience, and meaningful life orientation. The study contributes to Islamic psychology and Qur’anic studies by presenting tazkiyatun nafs as a spiritual-based model of mental resilience that connects classical Islamic concepts with contemporary psychological discourse.